Novel sizing and modeling techniques for synchronous reluctance machines - Murataliyev, Mukhammed (2021)
In recent years, there is a growing interest for high efficiency electric motors without, or with reduce content of, permanent magnets (PMs) for industrial applications. The Synchronous Reluctance (SynRel) machine is one of the most promising candidates that can meet the requirements of efficient and low cost drive [1]. The key benefits of this technology are a rotor structure made of flux barriers and iron parts, without excitation coils or PMs, like in induction motors (IM) and PM machines, respectively [2]. This leads to a cost effective structure that is using the reluctance principle to generate torque. The reluctance machine topology was introduced in 1920s, however has not been utilised at high industrial volumes yet due to superiority of the alternative technologies. IMs are considered as an industry “work horse”, which dominates the electrical machines market in applications such as industrial fans, pumps and mill type loads, as it is known to be the cheapest and the most reliable machine topology. On the other hand, PMs are mostly used in high performance applications, where the power-density is of the priority. Whereas, the interest in SynRel is mainly driven by lack of magnets or any other field excitation, as well as high efficiency [3], [4], [5]. The rare-earth permanent magnets began to commercialize for electrical motors in early 1980s. Various types of applications such as electric vehicles, wind turbines, actuators, started utilization of the PM synchronous machines [6], [7], [8]. Neodymium-iron-boron (NdFeB) permanent magnets are the common type for the high-performance applications due to their superior magnetic properties. In comparison the remanent flux density Br and coercivity Hc values of NdFeB are higher than any other type of magnets i.e. samarium-cobalt (SM2Co17), which was the major breakthrough in 1970s [9], and it is still extensively used when operating temperatures are very high. The main downfall of the NdFeB is the cost. The prices of the Neodymium had a huge spike in the mid-2011, as it was increased by factor of 25 compared to the beginning of 2010 [10], [11]. After hitting its peak, the price dropped rapidly and settled at its pre-bubble price [12]. Such price instability had a huge financial effect on PM machine manufacturers. Hence, as of 2019, there is a high research 4 emphasis on electrical machines with low volume of rare earth permanent magnet material [13], [14]. There is also a growing interest in very high efficiency, or super-premium efficiency electrical machines for the industrial sector [2], [15], [16]. This is driven by new requirements of the local governments for the industrial sector, as well as the world trend towards the reduction of the energy consumption and greenhouse gas emissions [17], [18]. Currently world leading manufacturers and R&D institutions are constantly investigating the possibility of increasing the efficiency using inexpensivee solutions. SynRel is a promising technology, which has features that are aligned with both research streams – high efficiency as well as lack of magnets [10], [12]. Leading manufacturing companies such as ABB (“Asea Brown Boveri”), KSB ("Klein, Schanzlin & Becker") and Siemens already started the serial production of the high efficiency SynRel. However, despite its advantages, there are still number of problems that are being investigated. From the machine design perspective, the main challenges of the topology come from the complex anisotropic structure of the rotor. Torque ripple, power factor and other secondary effects such as rotor iron losses, vibration and noise, are the main issues in SynRel [19], [20]. These issues mainly addressed using comprehensive analysis and optimization using FE. The proposed ideas and innovative techniques that are described in this thesis could significantly reduce time and effort required to design the SynRel machines. In some cases, it was shown that the time-consuming design optimization by means of FE can be bypassed. This is achieved by applying new dimensioning techniques, hence leading to a quick and effective design tools that is applicable for the wide power range machines.